The absence of a physical education textbook has an impact on raising the cognitive level of secondary school students. - fadhli, bedjaoui (sports creativity, 2025)
Books have become an important means of conveying scientific and educational knowledge and preserving information worldwide. They also play a role in developing the human mind in all aspects and are an active element in human life. Although physical education and sports have become a field of education and a powerful element in preparing the individual, providing them with broad experiences and skills that enable them to adapt to their society, guide their lives, and keep pace with the times, books remain a vital tool in human development.